P-11 Fibromyalgia: looking for markers and the impact of a multidisciplinary treatment. (18th November 2016) - Pareja, JL; Martin, F; Caceres, O; Blanco, M; Berral, FJ
Abstract : Objectives: Fibromyalgia syndrome (FM) is a complex chronic pain disorder of unknown origin. There are no biological markers to monitor FM progression and no permanent cure. Low-moderate physical exercise is a component of the evidence-based guidelines for its treatment. 1 Our aim was to identify markers associated with FM and its progression and to evaluate the efficacy of a multiapproach treatment, where physical activity is an important issue. Methods: The study is a treatment trial, open label and single centre, with 39 women (42 ± 4 years; range: 19-67 years) diagnosed for FM using the American College of Rheumatology Criteria. The study was approved by the Ethics Committee of the University Pablo Olavide. During the first visit FM diagnosis was made, together with all studies. Then, the treatment was prescribed for 66 ± 2 days and patients returned for FM severity diagnosis and same measurements. Patients were evaluated for anthropometric parameters, plasma cytokines values, intestinal permeability and clinical progression. The multiapproach treatment consisted on: i) Ubiquinol; ii) Nutritional complex (amino acids, vitamins and mineral); iii) Palmitoylethanolamide; iv) Synbiotic health supplement; v) Low intensity magnetic fields; vi) Food exclusion and vii) Physical activity (45-minutes walking/3-4 days a week at 60% of maximum heart rate). Analysis of variance (ANOVA) and paired and unpaired t -test were undertaken. P < 0.05 was considered significant. Pearson Product Moment correlation was calculated. Results: A significant improvement was observed after treatment as shown by Widespread Pain Index, Symptom Severity Score and Fibromyalgia Impact Questionnaire (FIQ) ( p < 0.001). No significant variations were observed, except for intracellular body water parameters, in anthropometric and body composition characteristics. Food-induced histaminosis release was observed to cow´s milk, egg, fruit, wheat, nuts and oily fish. Interleukin-1β (IL-1 β) and interleukin-6 (IL-6) plasma values were significantly higher in FM ( p < 0.001). When comparing the percentages of improvement of health status (FIQ) and interleukins reduction, the Pearson's correlation between the two variables showed a positive Pearson Product Moment correlation of 0.59 between FIQ and IL-1β reduction and of 0.62 between FIQ and IL-6 reduction. Patients with FM showed significant higher values ( p < 0.001) of intestinal permeability, that was significantly reduced ( p < 0.05) after treatment (Figure 1). Conclusions: i) There are different subsets of FM patients; ii) the use of intracellular body water, plasma cytokine values and intestinal permeability could be used as markers for FM progression; iii) food-sensitisation could be a mechanism for FM pathogenesis, iv) a multidisciplinary approach for FM treatment could be useful and v) moderate physical activity has an overall beneficial impact on the disease. Acknowledgment: The study was supported by Grupos PAI BIO-311 and CTS-595 from Junta de Andalucía. Reference: Garcia-Hermoso A, Saavedra JM, Escalante Y. Effects of exercise on functional aerobic capacity in adults with fibromyalgia syndrome: A systematic review of randomised controlled trials. J Back Musculoskelet Rehabil 2015 Oct;28 :609–19.